2007
DOI: 10.2110/jsr.2007.007
|View full text |Cite
|
Sign up to set email alerts
|

Outcrop Analog for Mixed Siliciclastic-Carbonate Ramp Reservoirs--Stratigraphic Hierarchy, Facies Architecture, and Geologic Heterogeneity: Grayburg Formation, Permian Basin, U.S.A.

Abstract: The Grayburg Formation (Late Permian, Guadalupian) is a shallow-marine succession flanking the Delaware and Midland basins of Texas and New Mexico, U.S.A. The Grayburg exemplifies the facies heterogeneity imparted by cyclic interbedding of siliciclastic and carbonate rocks from lithologically diverse, inner-ramp to outer-ramp facies assemblages. High-resolution correlation and mapping of laterally continuous Grayburg strata exposed in the Brokeoff Mountains, New Mexico, allow the stratigraphic architecture, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Lack of fossils and presence of vugs in this internally featureless microfacies indicate a low-energy, restricted lagoonal environment behind the high-energy sand shoals Amirshahkarami et al 2007; Barnaby and Ward 2007;Wanas 2008). This microfacies corresponds to the standard microfacies SMF-23 (non-laminated homogenous micrite and microsparite) and FZ 9 of Flügel (2004), typical of the shallow subtidal zone of a restricted, quiet water (lagoon) setting.…”
Section: Mudstone-wackestonementioning
confidence: 72%
See 3 more Smart Citations
“…Lack of fossils and presence of vugs in this internally featureless microfacies indicate a low-energy, restricted lagoonal environment behind the high-energy sand shoals Amirshahkarami et al 2007; Barnaby and Ward 2007;Wanas 2008). This microfacies corresponds to the standard microfacies SMF-23 (non-laminated homogenous micrite and microsparite) and FZ 9 of Flügel (2004), typical of the shallow subtidal zone of a restricted, quiet water (lagoon) setting.…”
Section: Mudstone-wackestonementioning
confidence: 72%
“…This microfacies is generally deposited during the regressive phase and records sea-level lowstands (Fischer and Sarnthein 1988;Barnaby and Ward 2007). Cycles at the bottom of the studied section are capped by this facies.…”
Section: Quartz Arenitic Sandstonementioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies of mixed clastic-carbonate systems have demonstrated the stratigraphic controls on sand-body accumulation (Kerans et al, 1994;McNeill et al, 2004;Barnaby and Ward, 2007;Phelps et al, 2008). In the Permian Basin of west Texas, bypass of eolian sand into downslope environments is well documented (Phelps et al, 2008).…”
Section: Clastic Inputmentioning
confidence: 96%